ETIKA PROFESI DAN BUDAYA SEKOLAH: FONDASI KINERJA GURU DI ERA PENDIDIKAN 5.0 - Andriyati, Sri Iin; Anjarsari, Afita; Susanti, Dewi Marya; Purnomo, Himawan Eko; Yuliarti, Rini (Institut Agama Kristen Negeri Toraja, 2025)
The transformation of the educational paradigm toward Education 5.0 requires a shift in the role of teachers from mere instructors to ethical, adaptive learning facilitators oriented toward humanistic values. This study aims to identify and synthesize the interrelationships among professional ethics, school culture, and teacher performance within the context of technology-based and human-centered educational transformation. This study employed an integrative literature review, analyzing 20 scientific articles published between 2019 and 2024 and indexed in SINTA and reputable international journals. The synthesis indicates that professional ethics provide a fundamental value framework that guides teachers’ integrity, accountability, and professionalism, while school culture functions as an ecosystem that supports the internalization of these values through a collaborative, disciplined, and quality-oriented environment. The integration of both dimensions creates synergy that strengthens teacher performance, particularly in professional responsibility, pedagogical innovation, and commitment to the quality of learning in the digital era. This study confirms that strengthening professional ethics and school culture is not only relevant as a normative discourse but also strategic as a foundation for fostering superior and sustainable teacher performance in the era of Education 5.0. Perubahan paradigma pendidikan menuju era Pendidikan 5.0 menuntut pergeseran peran guru dari sekadar pengajar menjadi fasilitator pembelajaran yang beretika, adaptif, dan berorientasi pada nilai-nilai kemanusiaan. Kajian ini bertujuan untuk mengidentifikasi serta mensintesis keterkaitan antara etika profesi, budaya sekolah, dan kinerja guru dalam konteks transformasi pendidikan berbasis teknologi dan humanisasi. Metode yang digunakan adalah integrative literature review dengan menganalisis 20 artikel ilmiah yang diterbitkan pada periode 2019–2024 dan terindeks SINTA maupun jurnal internasional bereputasi. Hasil sintesis menunjukkan bahwa etika profesi berperan sebagai landasan nilai yang menuntun integritas, akuntabilitas, dan profesionalitas guru, sementara budaya sekolah berfungsi sebagai ekosistem yang mendukung internalisasi nilai-nilai tersebut melalui iklim kolaboratif, disiplin, dan berorientasi mutu. Integrasi keduanya menghasilkan sinergi yang memperkuat kinerja guru, terutama dalam aspek tanggung jawab, inovasi pedagogis, dan komitmen terhadap mutu pembelajaran di era digital. Kajian ini menegaskan bahwa penguatan etika profesi dan budaya sekolah tidak hanya relevan sebagai wacana normatif, tetapi juga strategis sebagai fondasi kinerja guru yang unggul dan berkelanjutan di era Pendidikan 5.0.